Oil Price Shocks and Stock Market Booms in an Oil Exporting Country - Hilde C. Bjørnland (Norges Bank, 2008)
This paper analyses the effects of oil price shocks on stock returns in Norway, an oil exporting country, highlighting the transmission channels of oil prices for macroeconomic behaviour. To capture the interaction between the different variables, stock returns are incorporated into a structural VAR model, as stock prices are an important transmission channel of wealth in an oil abundant country. I find that following a 10 percent increase in oil prices, stock returns increase by 2.5 percent, after which the effect eventually dies out. The results are robust to different (linear and non-linear) transformations of oil prices. The effects on the other variables are more modest. However, all variables indicate that the Norwegian economy responds to higher oil prices by increasing aggregate wealth and demand. The results also emphasize the role of other shocks; monetary policy shocks in particular, as important driving forces behind stock price variability in the short term.
hdl:11250/2497769
Keywords: C32; E44; E52; 330; VAR; oil price shocks; monetary policy; stock market